Parallel Rough set approximation using map-reduce technique in Hadoop - Dubewar, Ankita (International Journal of Scientific Research and Management (IJSRM), 2015)
Rough set theory can be considered as a tool to study the uncertain, indescendent data by classifying the set into ternary classification as lower, upper and boundary region. This paper helps explaining the rough set theory using map-reduce in Hadoop. More over using some features we can reduce the number of input dimension, so that the process can be executed in comparative less time. Using this method we can help many organization that are facing problem related to the data handling and data analysis.